Individual Factors Including Age, BMI, and Heritable Factors Underlie Temperature Variation in Sickness and in Health: An Observational, Multi-cohort Study. Issue 9 (5th October 2021) - Penfold, Rose S; Zazzara, Maria Beatrice; Österdahl, Marc F; Welch, Carly; Ni Lochlainn, Mary; Freidin, Maxim B; Bowyer, Ruth C E; Thompson, Ellen; Antonelli, Michela; Tan, Yu Xian Rachel; Sudre, Carole H; Modat, Marc; et al.
Abstract: Background: Aging affects immunity, potentially altering fever response to infection. We assess effects of biological variables on basal temperature, and during COVID-19 infection, proposing an updated temperature threshold for older adults ≥65 years. Methods: Participants were from 4 cohorts: 1 089 unaffected adult TwinsUK volunteers; 520 adults with emergency admission to a London hospital with RT-PCR confirmed SARS-CoV-2 infection; 757 adults with emergency admission to a Birmingham hospital with RT-PCR confirmed SARS-CoV-2 infection and 3 972 adult community-based COVID Symptom Study participants self-reporting a positive RT-PCR test. Heritability was assessed using saturated and univariate ACE models; mixed-effect and multivariable linear regression examined associations between temperature, age, sex, and body mass index (BMI); multivariable logistic regression examined associations between fever (≥37.8°C) and age; receiver operating characteristic (ROC) analysis was used to identify temperature threshold for adults ≥ 65 years. Results: Among unaffected volunteers, lower BMI ( p = .001), and increasing age ( p < .001) was associated with lower basal temperature. Basal temperature showed a heritability of 47% (95% confidence interval 18%–57%). In COVID-19+ participants, increasing age was associated with lower temperatures in Birmingham and community-based cohorts ( p < .001). For each additional year of age, participants were 1% less likely to demonstrate a fever ≥37.8°C (OR 0.99; p < .001). Combining healthy and COVID-19+ participants, a temperature of 37.4°C in adults ≥65 years had similar sensitivity and specificity to 37.8°C in adults <65 years for discriminating infection. Conclusions: Aging affects temperature in health and acute infection, with significant heritability, indicating genetic factors contribute to temperature regulation. Our observations suggest a lower threshold (37.4°C/97.3°F) for identifying fever in older adults ≥65 years.